A systematic literature review on implementation of GeoGebra: Benefits and challenges in mathematics education - Azis, Yunia Mulyani; Rohaeti, Euis Eti (Jurnal Infinity, 2025)
GeoGebra is a popular dynamic geometry software that is used by many teachers and students throughout the globe to understand mathematical concepts better. Its versatility to be used online and offline has opened up a new horizon in multiple learning environments in the mathematics education field. Whether it is blended, online, or even in a traditional learning environment, a literature study regarding its benefits and challenges is still relatively rare. This study follows a Systematic Literature Review (SLR) by utilizing PRISMA's meta-synthesis formulation to identify the benefits and challenges of the application of GeoGebra in different learning environments, which initially identify 527 literature and through a deep screening inclusion and exclusion criteria, a result of matching 33 literature studies has selected and shown that the most mentioned benefits of GeoGebra in multiple learning environment are its capabilities to improve mathematical concept understanding, while the most mentioned challenges itself is showing a requirement for supplementary module to assist GeoGebra implementation. These findings are crucial for teachers or educational institutions to set up a better learning component, media, or tools before integrating GeoGebra into the learning process.